The digital divide issues: is the gap getting bigger? - Mohd Nizam Osman, (2007)
This paper addresses the digital divide issues based on a survey of 150 respondents comprising of governments and respondents from rural and urban sectors of selected areas as well as in-depth interviews. The study explored various government measures to encourage the wider uptake of computers and other forms of ICT applications. The study also looked into steps taken to minimize the digital divide gap between residents residing across the rural and urban parts of the country. From the study, it is obvious that the various measures introduced by the government have not been effective in minimizing the digital divide gap between the residents. Clearly, the findings of the study also revealed that the objectives of some of the measures introduced by the government were largely seen as strategic. However, in terms of the planning and implementation mechanisms, the government will need to put in more effort, especially in terms of coordination between the government and other implementation bodies.